Implementasi Kepemimpinan Kepala Sekolah dalam Membina Kinerja Guru - Rina Yuliana; Cahya Syaodih; Rita Sulastini (Departement of Mathematics Education, 2023)
The Covid 19 pandemic which began to spread in Indonesia at the end of 2019 had a major impact on the world of education. With the outbreak pandemic, it has spawned new innovations, namely technology-based learning and internet networks. The essence of the problem formulation in this study is the leadership of the Principal in fostering teacher performance. The problem of improving teacher performance is an unresolved problem in line with the complexity of environmental changes, both in terms of planning, implementation and evaluation. The theological basis in the Al-Qur'an letter Al-Muj is verse 11 and the words of the Prophet Muhammad SAW which means